Forward (Jewish Thought, 2021)
It is with great pride that we present the third issue of the annual journal, Jewish Thought, sponsored by the Goldstein-Goren International Center for Jewish Thought, at Ben-Gurion University of the Negev. This issue focuses on the topic of asceticism in Judaism and the Abrahamic religions. It consists of 14 articles – 6 in Hebrew and 8 in English. Many of the contributions are based on lectures on this topic given at the international workshop, "Ascetic Trends in the Abrahamic Religions in the 13th Century," that took place in November 2019, and was sponsored by the Israel Science Foundation, Goldstein Goren International Center for Jewish Thought and Center for the Study of Relations Between Jews, Christians , Muslims. The workshop was organized by Prof. Oded Yisraeli from the Goldstein-Goren Department of Jewish Thought at Ben-Gurion University, and Prof. Avriel Bar-Levav from the Department of History, Philosophy and Jewish Studies at the Open University, both of whom were invited to be guest editors of this issue. We would like to thank the Center for the Study of Relations between Jews, Christians, Muslims at the Open University for its generous support in the publication of this issue. Most of the articles in this issue were written by established scholars, while some were written by young scholars who are at the beginning of their scholarly career. All articles that were submitted, whether from conference participants or not, underwent a rigorous selection process involving at least two reviewers. Several months ago, we were all saddened to learn of the passing away of Alex Goren. Among his many significant contributions to Ben Gurion University of the Negev, Alex assisted his father Avram in the establishment of the Goldstein-Goren International Center for Jewish Thought. After the death of Avram, Alex, with the aid of his siblings, assumed responsibility for overseeing the activities of the center and lending invaluable assistance in times of crises. He will be missed by all of us. To his memory we devote this issue.